Development of Edu Uno-Based Teaching Aids to Improve Critical Thinking on the Subject of Types and Patterns of Decorative Art in V Grade Elementary School - Listiya Damayanti Permatasari; Ageng Triyono; Titi Anjarini (LPPM STKIP Kusuma Negara, 2026)
The lack of critical thinking skills among fifth-grade elementary school students in comprehending creative content on types and patterns of decorative motifs necessitates the development of Edu Uno-based teaching aids as interactive learning media. This study aims to develop Edu Uno game-based instructional tools to enhance students' critical reasoning on the aforementioned material. The approach employed is the Research and Development (R&D) model adapted from ADDIE, validated by media experts (score: 4.57) and material experts (score: 4.65), both deemed highly feasible. Limited trials on 10 students yielded 62.69% effectiveness (moderate category), while field trials on 21 students achieved 73.16% (high category), with N-Gain scores in the high category. Questionnaire results from 31 students (98.6%) and one teacher (100%) indicated that the teaching aids are highly practical and suitable for sustained use. This development is expected to serve as an innovative solution for improving learning quality and student competency achievement effectively.